BOTTAZZI, Tamara; BRESSAN, Raquel; FLORES, Pedro; MAFFEI, Ana Laura; PAUL, Andrea; QUEREJETA, Giselle; REALE, Marcela y SILVA Jeremías. (2020) El desafío de la interdisciplinariedad en la investigación. La ciencia y el tiempo. Ediciones de la Universidad - De Leo, Mariano (Espacio Abierto, 2021)
.